2013
DOI: 10.1021/ol400917j
|View full text |Cite
|
Sign up to set email alerts
|

Ready Synthetic Access to Enantiopure Allylic α(F)-Branched Fluoroalkenes

Abstract: Convenient access to homochiral fluoroalkenes is described via a Julia-Kocienski olefination reaction. The required homochiral fluorosulfone is synthesized by a Mitsunobu reaction from readily available enantiopure secondary alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…To test our hypothesis, we selected gem -difluoroalkene 2a as an alkenylating reagent to react with 1-bromo-2-phenylethane 1a (Table 1). After careful evaluation of the reaction parameters, we found that a combination of inexpensive and bench-stable Ni(ClO 4 ) 2 ·6H 2 O as a pre-catalyst, 6,6′-dimethyl-2,2′-bipyridyl ( L1 ) as a ligand, and Mn as a reducing agent to generate Ni 0 in DMA at 25 °C gave the benzylic fluoro-alkenylation product 3a with Z -configuration in 28% NMR yield within 12 hours (entry 1) 12. Pleasingly, the product was obtained with excellent regioselectivity and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…To test our hypothesis, we selected gem -difluoroalkene 2a as an alkenylating reagent to react with 1-bromo-2-phenylethane 1a (Table 1). After careful evaluation of the reaction parameters, we found that a combination of inexpensive and bench-stable Ni(ClO 4 ) 2 ·6H 2 O as a pre-catalyst, 6,6′-dimethyl-2,2′-bipyridyl ( L1 ) as a ligand, and Mn as a reducing agent to generate Ni 0 in DMA at 25 °C gave the benzylic fluoro-alkenylation product 3a with Z -configuration in 28% NMR yield within 12 hours (entry 1) 12. Pleasingly, the product was obtained with excellent regioselectivity and stereoselectivity.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, Lequeux and co-workers developed the synthesis of different Julia-Kocienski reagents via a Mitsunobu reaction with secondary alcohols followed by a Krapcho decarboxylation. 60 The olefination reaction with these reagents gave enantiopure monofluoroalkenes containing a chiral allylic substituent in moderate to good yields. Using aromatic aldehydes, E-alkenes were obtained as the major isomers, while the Z-alkenes were obtained as the major isomers using aliphatic aldehydes (Scheme 45).…”
Section: Using Benzothiazol-2-yl Sulfonesmentioning
confidence: 99%
“…In addition, their preparation has been reported from chiral sulfones via the Julia-Kocienski reaction (Scheme 17). 28 The sulfones, prepared by Mitsunobu alkylation reaction, were reacted with aliphatic and aromatic aldehydes to afford enantiopure allylic fluoroalkenes in good yields, but moderate to good Z/E selectivity (nearby 3:7).…”
Section: Short Review Syn Thesis 28 Monofluoroalkenes With An α-Stermentioning
confidence: 99%